The Elements of Exclusivism in Christian Tradition - Qodratullah Qorbani (Pizhūhish/hā-yi Falsafī- Kalāmī, 2020)
Introduction Religious exclusivism is based on some Christian theological teachings that are derived from the Bible which were introduced through some early Christian theologians’ viewpoints; like Saint Paul. This theological approach emphasizes on exclusive religious truthfulness and salvation, and denies and deprives other religious traditions of participating in divine truthfulness and salvation. In this paper, we try to show some essential roots and elements of Christian exclusivism and some outcomes that it can introduce for the Christian world and Christians’ dialogue with other religions. Summary Christian exclusivism is rooted in some Christian teachings, which are as follows: 1. Some verses of the Bible refer to it, 2. It is based on historical facts regarding the life of Jesus Christ, 3. It indicates direct interference of God to save his children, 4. It relies on some religious beliefs such as Trinity, Atonement, Resurrection of Jesus and Incarnation, 5. It depends on the centrality of Jesus Christ’s role, 6. It shows the high place of the Church and the Pope, 7. It pays more attention to faith and divine grace than legal duties. When we refer to the Bible, we see that there are some verses that confirm religious exclusivism; for example, in the book of John, it is said that there is no way to salvation except through Jesus. The Bible also says Jesus was born, suffered and crucified and died to save Christians and to remove their original sin. In fact, God has decided to send his son, namely Jesus, for removing and clearing the original and inheritable sins of his children; since without sending Jesus and his death, it was not possible to save his children. Therefore, Divine interference was necessary for saving his believers. Based on the aforementioned teachings, Christian theologians argue that there are some teachings that pertain to religious exclusivism. Teachings like the Trinity, Incarnation, Atonement, Grace, Faith and the Resurrection of Jesus can be considered in this case. The teaching of Trinity teaches us that God, the Holy Spirit, and Jesus are the same and have an equal divinity. Based on this teaching, Jesus has acquired a divinity equal to God. The teaching of Incarnation says that God has been embodied and shaped in the body of Jesus and accepted some corporeal virtues in order to save his children. The teaching of Atonement indicates that through crucifixion and the death of Jesus, all the sins of the children of God were forgiven and then they are considered as innocent servants of God. It is important to know that the later Christian theologians and communities have tried to find many religious justifications regarding such teachings. They have discussed and confirmed these teachings in many Christian councils during the last 20 centuries. The next element is Jesus Christ’s central role regarding God’s project for saving his children. It means saving people was possible through Jesus alone; he is the only one who was worthy and suitable for actualizing such a divine program. So, he is the only way for the salvation of God’s children. Then, if we believe in such historical facts regarding Jesus’ birth, suffering, crucifixion, and final resurrection, we can be considered as his believers and all of our sins will be forgiven. Hence, Christians pay more attention to loving Jesus, Divine grace, and faith more than following religious rules. They believe that Jesus Christ has released them from legal laws through his crucifixion and suffering. The last element is the significant role and place of the Church and the Pope regarding the classic interpretation of the Bible and introducing the unique path of salvation. In this case, Catholic Christians believe that salvation is possible only through the Catholic Church and the Pope; whereas, Protestant Christians emphasize believing in Jesus alone as the only way for salvation. The combination and reciprocal cooperation of the aforementioned elements hase established and strengthened Christian Exclusivism from the early periods of Christianity up to recent centuries. The historical growth of Christian exclusivism has gradually led to some irrational and unpleasant outcomes. Some of them are: ignoring the realities and values of other religions, the disinclination of the Christians to listen and learn about other religions’ teachings and values, believing in extreme holiness regarding Christian teachings and avoiding thinking about their rationality, introducing a Christian’s identity to be based on negating other religions’ identity, welcoming ideological missionaries to invite others to Christianity and considering others as disbelievers who should accept the Christian invitation and evangelism. The way to exit Christian Exclusivism is to rethink the Christian teachings that led to exclusivism; especially teachings like the Trinity, Incarnation, Crucifixion, Atonement, the Church and so on. Christians also should try to study about other religions’ realities and facts through their eyes; not Christian eyes. They should emphasize on spreading dialogue between Christianity and other religions in order to recognize each others’ virtues, and to reform their own irrational teachings. Finally, all Christians and adherents of other religions, in particular, Muslims and Jews should note that God has willed to guide all of them and bestowed the grace of truthfulness and salvation to them based on their capacities. So most, or all the people of the world, have benefited from divine grace concerning truthfulness and salvation gradually; not exclusively.